P6.072 Differences Among Canadian Family Practitioners by Years of Practise in Uptake of Sexually Transmitted and Blood-Borne Infections (STBBIs) Clinical Recommendations. (13th July 2013) - Seto, J; Kapral, O; Wong, T; Gale-Rowe, M; Demers, A; Dodds, J; Fisher, W; Steben, M; Read, R
Abstract : Background: Clinical guidelines play a critical role in the prevention and control of sexually transmitted and blood-borne infections (STBBIs). Little is known in Canada as to the uptake of clinical recommendations and the comfort-level of family practitioners performing STBBI-related clinical tasks. Methods: To evaluate the prevention and control of STBBIs by family practitioners, information was elicited from a convenience sample (N = 207) of family practitioners at a national Canadian family medicine forum in Toronto between November 15 and 17, 2012 using two methods: audience response systems (during a symposium) and a self-administered questionnaire at an exhibition booth. Analysis was stratified by years of practise to identify any differences in STI risk assessments, treatment of gonorrhoea and offering of HIV testing. The Fisher's exact and chi-square tests were used to determine statistical significance. Results: Approximately 26.3% of early-career-practitioners (< 5-yrs) and 15.9% mid-to-late-career-practitioners (≥ 5yrs) reported doing an STI risk assessment during a health exam (p = 0.08). Overall, in their treatment of choice for gonorrhoea, most selected cefixime (52.2%; ceftriaxone: 19.5%; and azithromycin: 15.1%). More early-career-practitioners selected cefixime than mid-to-late-career-practitioners (51.5%; 48.4%, respectively; p = 0.2). In the past year, a greater proportion of mid-to-late-career (54.3%) than early-career-practitioners (40.8%; p = 0.05) reported that they offered HIV testing to 10%–or-less of their patients. A comparable percentage of early-career (25.5%) and late-career (20.3%) practitioners said they offered HIV testing to 50%–or-more of their patients (p = 0.3). After learning about upcoming new HIV screening and testing recommendations, 50.2% of early-career compared to 35.7% of mid-to-late career practitioners said they would offer HIV testing more often (p = 0.07). More early-career-practitioners (48.5%) were willing to offer an HIV test while testing for other STIs compared to mid-to-late-career-practitioners (41.7%; p = 0.3). Conclusions: Results indicate a need to improve uptake of STI and HIV clinical recommendations among all practitioners, but particularly among mid-to-late-career practitioners.